Analisis User Experience Aplikasi SIPON CERIA RSUD Dr Darsono dengan menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) - Gumilar Hendra Kusuma; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
RSUD Dr. Darsono is a Regional General Hospital in Pacitan Regency. In improving services, RSUD Dr. Darsono utilizes mobile-based technology, namely the SIPON CERIA application. Users who are members of the Pacitan Regency community have problems using the application. Based on the existing problems, researchers conducted research on user experience analysis on the SIPON CERIA application. By using the usability testing and user experience questionnaire (UEQ) methods, it is hoped that the user experience analysis process for the SIPON CERIA application can be carried out. The usability testing was carried out on 3 users of the SIPON CERIA application with the result that the  effectiveness aspect obtained a value of 100% and meant that the user could complete the task given by the researcher, in the efficiency aspect it obtained a value of 100% and meant that the overall time obtained in carried out the task well enough and on the aspect of satisfaction with the system usability scale (SUS) questionnaire obtained a result of 69.16 and this means that the SIPON CERIA application has a marginally high level of user satisfaction. Then the UEQ questionnaire was distributed on user experience testing which was given to 20 respondents and obtained an average score of 1.170 on the six aspects of the ueq questionnaire, namely the aspects of interestingness, perspicuity, efficiency, stimulation, novelty and dependability which means that users of the SIPON CERIA application provide assessment of the positive direction.